Both moderate and severe exacerbations accelerate physical activity decline in COPD patients. Issue 1 (25th January 2018) - Demeyer, Heleen; Costilla-Frias, Marcos; Louvaris, Zafeiris; Gimeno-Santos, Elena; Tabberer, Maggie; Rabinovich, Roberto A.; de Jong, Corina; Polkey, Michael I.; Hopkinson, Nicholas S.; Karlsson, Niklas; Serra, Ignasi; Vogiatzis, Ioannis; et al.
Physical activity (PA) is a relevant outcome measure in chronic obstructive pulmonary disease (COPD). Low PA is prevalent and drives prognosis [1]. Unfortunately, the determinants of PA and its change over time are poorly understood [1]. The fact that the PA progressively declines over time along with worsening of lung function and health status [2] suggests that the PA decline could be due to the progression of the disease and specifically to acute exacerbations [3]. An acute reduction in PA at the onset has been reported both in severe exacerbations requiring a hospitalisation [4] and in ambulatory treated exacerbations [5, 6]. A sustained PA reduction has been shown 1 month after hospital discharge [4] whereas PA almost returns to stable levels after community-treated exacerbations [6]. One study found faster PA decline in patients with a history of two or more exacerbations in the 12 months prior to the study [5]. This analysis did not adjust for confounders of the association ( e.g. airflow obstruction, symptom burden) or external variables influencing PA ( e.g. climate). It could also be argued that the greater decline in PA was due to lower health status at baseline. Although PA is an important outcome for COPD patients, little is known about the role of exacerbations in patients' experience of PA. Importantly, both the amount of activity and difficulties experienced during activity are integral to the concept of PA limitation [7]. The aim of the present analysis was to assess the association between the number and severity of exacerbations and changes in PA and PA experience. Exacerbations have a negative impact on long-term daily physical activity of COPD patients http://ow.ly/olGl30hkdMl